Represent yourself in court : prepare & try a winning civil case - Bergman, Paul, 1943-; Berman, Sara J., 1964- (Nolo, 2025)
Many disputes are too big for small claims court but too small to jsutify a lawyer's fee. Fortunately, if you're willing to learn the courtroom ropes, you can successfully handle your own case from start to finish. Represent Yourself in Court breaks the pretrial and trial process down into easy-to-understand steps. Armed with these clear and thorough instructions, you'll be well prepared to: Draft and file court papers ; Get help from an attorney or legal coach ; Obtain and prepare your evidence, including social media postings ; Handle depositions ; Line up, prepare, and examine witnesses ; Present an opening statement ; Make and respond to objections ; Pick a jury if necessary, and ; Deal with the court clerk and judge. Whether you're a plaintiff or a defendant, this book will help you handle a bankruptcy, divorce, landlord-tenant dispute, breach of contract case, small business dispute--or any other civil lawsuit. The 12th edition is completely updated to include remote court appearances.